2022
DOI: 10.3390/c8040071
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hybrid Modification with Humic Acids of Environmentally Safe Biodegradable Hydrogel Films Based on Hydroxypropyl Methylcellulose

Abstract: The possibility of increasing the complexity of the operational properties of environmentally safe biodegradable polymer hydrogel materials based on hydroxypropyl methylcellulose due to modification by humic acids from lignite is considered. As a result of this research, environmentally safe hybrid hydrogel films with antibacterial properties were received. In the framework of physicochemical studies, it was determined by IR spectroscopy that hydroxypropyl methylcellulose modified with humic acids hybridmateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The obtained results showed that the antimicrobial performance improves by increasing the HS amount within the hybrid gels. In addition, gels treated with EDC exhibit a higher inhibition diameter and lower MIC values compared to those of the corresponding physical gels, suggesting that the hybrid modification with HS using EDC chemistry allows for the reduction in their water absorption and gives them better antibacterial properties . Indeed, the higher antimicrobial capacity of humic gels was related to the chemical cross-linking between gelatin and HS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results showed that the antimicrobial performance improves by increasing the HS amount within the hybrid gels. In addition, gels treated with EDC exhibit a higher inhibition diameter and lower MIC values compared to those of the corresponding physical gels, suggesting that the hybrid modification with HS using EDC chemistry allows for the reduction in their water absorption and gives them better antibacterial properties . Indeed, the higher antimicrobial capacity of humic gels was related to the chemical cross-linking between gelatin and HS.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, gels treated with EDC exhibit a higher inhibition diameter 74 and lower MIC values compared to those of the corresponding physical gels, suggesting that the hybrid modification with HS using EDC chemistry allows for the reduction in their water absorption and gives them better antibacterial properties. 83 Indeed, the higher antimicrobial capacity of humic gels was related to the chemical cross-linking between gelatin and HS. Notably, larger water uptake determined by HS cross-linking at large HS content might enable better exposure of active moieties and determine a more effective biocide action.…”
Section: Resultsmentioning
confidence: 99%
“…The swelling degree of smart biologically active polymeric transdermal hydrogel was calculated according to the following formula [10]:…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, nanocellulose promoted bioadhesion and cell growth in the smart hydrogel medium. In addition, in our previous work, it was proved that humic substances, due to their ability to cross-link some polysaccharides and proteins, are materials that improve not only the mechanical properties of polymer hydrogels but also directly affect such hydrogel properties as transdermal ability [9,10].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation